ORGANIZATIONAL SUPPORT OF INTELLECTUAL PROPERTY MANAGEMENT AT THE ENTERPRISE - I. Kornilova; V. Svyatnenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article deals with theoretical issues of organizational support of intellectual property management at the enterprise. It is defined the nature, goals, objectives organization of intellectual property. It is selected the features, factors of influence on the choice of organizational structure and organizational form of intellectual property management on an enterprise. It is proposed systematization forms of organizational maintenance of intellectual property management at different classification criteria. Attention is paid to consider outsourcing forms of operations with intellectual property.